Assessing the impact of First Episode Rapid Early Intervention for Eating Disorders on duration of untreated eating disorder: A multi‐centre quasi‐experimental study. (28th October 2020) - Flynn, Michaela; Austin, Amelia; Lang, Katie; Allen, Karina; Bassi, Ranjeet; Brady, Gabrielle; Brown, Amy; Connan, Frances; Franklin‐Smith, Mary; Glennon, Danielle; Grant, Nina; Jones, William Rhys; et al.
Abstract: Background: Duration of untreated eating disorder (DUED), that is, the time between illness onset and start of first evidence‐based treatment, is a key outcome for early intervention. Internationally, reported DUED ranges from 2.5 to 6 years for different eating disorders (EDs). To shorten DUED, we developed FREED (First Episode Rapid Early Intervention for EDs), a service model and care pathway for emerging adults with EDs. Here, we assess the impact of FREED on DUED in a multi‐centre study using a quasi‐experimental design. Methods: Two hundred and seventy‐eight patients aged 16–25, with first episode illness of less than 3 years duration, were recruited from specialist ED services and offered treatment via FREED. These were compared to 224 patients, of similar age and illness duration, seen previously in participating services (treatment as usual [TAU]) on DUED, waiting times and treatment uptake. Results: FREED patients had significantly shorter DUED and waiting times than TAU patients. On average, DUED was reduced by ∼4 months when systemic delays were minimal. Furthermore, 97.8% of FREED patients took up treatment, versus 75.4% of TAU. Discussion: Findings indicate that FREED significantly improves access to treatment for emerging adults with first episode ED. FREED may reduce distress, prevent deterioration and facilitate recovery. Highlights: This study is a large‐scale replication of an earlier single‐centre pilot study of First Episode Rapid Early Intervention for Eating Disorders (FREED). Findings indicate that, as in the pilot study, FREED significantly reduces duration of untreated eating disorder and is associated with significantly shorter wait times for both assessment and treatment when implemented at scale Differences between groups were more pronounced when systemic delays were minimal The proportion of FREED patients taking up treatment was significantly higher than in treatment as usual, suggesting that a shorter interval between help‐seeking from primary care and an offer of specialist assessment/treatment has clear down‐stream benefits